Emotional abuse among Lesbian Italian women: Relationship consequences, help-seeking and disclosure behaviors. Issue 2 (3rd April 2021) - Battista, Silvia Di; Paolini, Daniele; Pivetti, Monica; Biondi, Paola; Balsamo, Michela; Carlucci, Leonardo; Cigliano, Ileana Aiese; Mazzoni, Silvia
Abstract: Objective: The study aims to provide a preliminary examination of the psychometric properties of the Italian version of Multidimensional Measure of Emotional Abuse (MMEA) and aims to investigate consequences of emotional abuse for the relationship, help-seeking and disclosure behaviors, among a sample of lesbian women. Methods and participants: One hundred and sixty-five lesbian volunteers filled in a self-report questionnaire including a measure of emotional abuse (MMEA) investigating the consequences of the abuse for the relationship and their disclosure and help-seeking behaviors. Results: Structural equation modeling (SEM) confirmed the four-factor structure of the MMEA among the sample, and indicated MMEA as a valid tool to measure the phenomenon among Italian lesbian women. As for the consequences of the emotional abuse, most of the participants continued their relationship after the abuse and chose not to talk about the episodes to anyone. When opening up about the abuse, participants mainly reported it to close friends and psychologists and/or psychotherapists. These results have important clinical and policy implications as they provide some indications to be taken into account by mental health professionals and policymakers working with abused lesbian clients.